Pengaruh Independensi, Kompetensi, dan Profesionalisme Auditor terhadap Kualitas Audit: - Sri Trisnaningsih; Diarany Sucahyati; Iftinandea Wresti Rosyadi (Reslaj : Religion Education Social Laa Roiba Journal, 2023)
In order to determine the effects of auditor independence, auditor competence, and auditor professionalism on the audit quality conducted by individuals working for Public Accounting Firms (KAP) that are officially listed in the Indonesian Institute of Public Accountants (IAPI) in Surabaya, this study will examine these factors. This study used a quantitative technique and a sample of 63 people that was selected using the Slovin formula and the fundamental random sampling methodology. The distribution of questionnaires was the main way that data were gathered for this study. The approaches for data analysis in this study employed partial least square (PLS) data management software. The results of this study show how professionalism, independence, and competency affect audit quality. As independence, skill, and professionalism rise, the audit quality rises. Keywords: Audit Quality, Independence, Competence, Professionalism